Esomeprazole and pantoprazole enhance the antiproliferative effects of cisplatin on the human neuroblastoma SH-SY5Y cell line - Karademir, Mustafa; Ergül, Merve (International Journal of Research in Medical Sciences, 2019)
Background: Proton pump inhibitors (PPIs) largely used a drug to treat gastroesophageal disease such as gastric ulcers. Moreover, in recent years, several studies suggest that PPIs have an important anti-cancer effect in monotherapy and or combination with chemotherapy. The aim of this study was to investigate whether esomeprazole and pantoprazole exhibit anti-cancer effect alone or could enhance chemosensitivity on the human neuroblastoma cell line SH-SY5Y to cisplatin. Methods: The human neuroblastoma SH-SY5Y cells were cultured and treated with different concentrations of esomeprazole, pantoprazole, and cisplatin alone. Also, these cells exposed to cisplatin+ esomeprazole and cisplatin + pantoprazole combinations, respectively and incubated 24 h. The antiproliferative activities of the (PPIs) alone or in a combination of cisplatin was evaluated using the XTT colorimetric assay. Results: According to experimental data, neither PPIs showed no cytotoxicity on the human neuroblastoma cell line SH-SY5Y at all concentrations. However, when combined with cisplatin separately, they were found to have significant antiproliferative effects on the human neuroblastoma SH-SY5Y cell lines when compared to cell lines treated with cisplatin alone (p<0.05). Conclusions: Taken together, the inhibition of V-ATPase via esomeprazole and pantoprazole might enhance the chemosensitivity of cisplatin on the human neuroblastoma cell line SH-SY5Y. However, further studies are needed to be able to utilize PPIs in human neuroblastoma cells.